Dissolving an ambiguous partnership - Oechssler, Joerg; Roomets, Alex (AWI discussion paper series, 2023)
Two partners try to dissolve a partnership that owns an asset of ambiguous value, where the value is determined ex post by a draw from an Ellsberg urn. In a within-subject experiment, subjects make decisions in three different bargaining mechanisms: unstructured bargaining, the Texas shoot-out, and a K + 1 auction. We find that the K +1 auction is the most e¢ cient mechanism, which is in line with theory. Free format bargaining yields a surprising number of disagreements, which are not usually observed when the partnership has a certain or risky value.
Keywords: Graue Literatur